Lipid recovery from oleaginous yeasts: Perspectives and challenges for industrial applications. (1st January 2020) - Khot, Mahesh; Raut, Gouri; Ghosh, Debashish; Alarcón-Vivero, Manuel; Contreras, David; Ravikumar, Ameeta
Highlights: Yeast lipid recovery is highly dependent on cell wall composition. High mannan/chitin content makes oleaginous yeast more resistant to lysis. Different extraction processes are needed for each yeast to define its lipid yield. Cell wall modification can improve the harvesting and cell susceptibility to lysis. Yeast cell wall polysaccharides is an industrially important byproduct. Abstract: Oleaginous yeasts are promising candidates for generating renewable fatty acid-based fuels and oleochemicals. The quantitative recovery of the total intracellular lipid from the yeast cell is a critical step to their subsequent analysis and development of a bioprocess. However, the scalable process for lipid recovery from either wet or dry yeast biomass is far from commercialization. The major drawback for this is its rigid cell wall with high chitin and mannan content, which makes the oleaginous yeast cell resistant to lysis. Multiple procedures have been developed for the extraction of yeast lipids each with its limitations. Hence, a better understanding of the cell wall composition and knowledge of cell wall chemistry would provide information to aid in the design of better protocols for oil extraction. This review attempts to integrate both conventional and newly published oleaginous yeast biomass conditioning methods from extraction protocols into a unified body of knowledge. Existing lab-scale physical, chemical, and mechanical pretreatment methods for cell-mass were described and compared. A road-map based on cell wall modification approach is proposed for enhanced cell harvesting and lipid extraction from an oleaginous yeast species.